Financial Literacy Understanding and Simple Financial Report Preparation at SMKN 11 Bandung - Nastiti Rizky Shiyammurti; Zalfa Qathrunnada; Sabieq Almas Muafi; Defan Maulana; Tiara Putri Aurelia; Imas Maesyaroh (Edumedia Solution, 2026)
Financial literacy is a crucial competency for students to support their personal financial management skills and prepare them for the workplace and entrepreneurship. However, students still lack understanding of the basic concepts of financial management and the preparation of simple financial reports. Therefore, this community service activity aims to improve students' understanding of financial literacy and skills in preparing simple financial reports at SMKN 11 Bandung. The activity was implemented through an educational and participatory approach, including material delivery, interactive discussions, practical training in preparing simple financial reports, and direct mentoring for participants. The material provided included an introduction to financial literacy, income and expense management, the importance of financial planning, and techniques for preparing simple financial reports, including transaction recording, income and expense reports, and simple profit and loss statements. The results of the activity demonstrated an increase in participants' understanding of the concept of financial literacy and their ability to systematically prepare simple financial reports. Participants also demonstrated high enthusiasm throughout the training and mentoring process. Thus, this activity positively contributed to improving students' financial competency, preparing them to face future economic challenges, and supported the development of an entrepreneurial spirit within the school environment. Keywords: financial literacy, simple financial reports, mentoring, vocational high school students, community service.